Risk factors for a first thrombotic event in antiphospholipid antibody carriers. A multicentre, retrospective follow-up study. Issue 3 (23rd September 2008) - Ruffatti, A; Ross, T Del; Ciprian, M; Nuzzo, M; Rampudda, M; Bertero, M T; Bergia, R; Caramaschi, P; Biasi, D; Capsoni, F; Montaguti, L; Ruffini, R; et al.
Abstract : Objectives: To asses risk factors for a first thrombotic event in antiphospholipid antibody (aPL) positive carriers and evaluate the efficacy of prophylactic treatments. Methods: Recruitment criteria were age 18–65 years, no history of thrombosis, positivity for lupus anticoagulant and/or IgG/IgM anticardiolipin antibody (aCL) on ⩾2 occasions at least 6 weeks apart. Demographic, laboratory and clinical parameters were collected at enrolment and at the time of the thrombotic event. Results: 370 patients/subjects (mean (SD) age 34 (9.9) years) were analysed retrospectively for a mean (SD) follow-up of 59.3 (45.5) months. Thirty patients (8.1%) developed a first thrombotic event during follow-up. Hypertension and medium/high levels of IgG aCL were identified by multivariate logistic regression analysis as independent risk factors for thrombosis. Thromboprophylaxis during high-risk and long-term periods was significantly protective. Conclusions: Hypertension or medium/high titres of IgG aCL are risk factors for a first thrombotic event in asymptomatic aPL carriers and primary prophylaxis is protective.